2013
DOI: 10.1111/2049-632x.12076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of YadC protein delivered by live attenuatedSalmonellaas a vaccine against plague

Abstract: Yersinia pestis YadB and YadC are two new outer membrane proteins related with its pathogenicity. Here, codon optimized yadC, yadC810 (aa 32-551) or yadBC antigen genes delivered by live attenuated Salmonella strains are evaluated in mice for induction of protective immune responses against Y. pestis CO92 through subcutaneous (s.c.) or intranasal (i.n.) challenge. Our findings indicate that mice immunized with Salmonella synthesizing YadC, YadC810 or YadBC develop significant serum IgG responses to purified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…But immunization with the GST-YadC 137–409 protein, which fused YadC aa 137 to 409 to C terminal of glutathione S-transferase (GST), provided partial protection against F1 − Y. pestis challenge in mice and was found to stimulate mixed Th1/Th2 responses [51]. However, Sun et al showed that YadC810 protein immunization could not provide any protection against subcutaneous and intranasal challenge of virulent Y. pestis CO92 [52]. The explanations for this contrary result: 1) the higher challenge dose we used; 2) the YadC protein (aa 32–551) used for immunization in our studies was different with the YadC protein (aa 137–422) used by Murphy et al [51].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…But immunization with the GST-YadC 137–409 protein, which fused YadC aa 137 to 409 to C terminal of glutathione S-transferase (GST), provided partial protection against F1 − Y. pestis challenge in mice and was found to stimulate mixed Th1/Th2 responses [51]. However, Sun et al showed that YadC810 protein immunization could not provide any protection against subcutaneous and intranasal challenge of virulent Y. pestis CO92 [52]. The explanations for this contrary result: 1) the higher challenge dose we used; 2) the YadC protein (aa 32–551) used for immunization in our studies was different with the YadC protein (aa 137–422) used by Murphy et al [51].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…With the exception of two additional plasmids (pPCP1 and pMT1) carried by Y. pestis, the two species share Ͼ95% genetic identity and a common virulence plasmid with a conserved colinear backbone (30). BLAST analysis of several major Y. pestis antigens showed that LcrV shares 96% amino acid identity between the two species and that Psn and YadC, two additional antigens shown to be protective against Y. pestis challenge (31)(32)(33), share 100% homology (34) and Ͼ97% homology (35), respectively. Furthermore, Y. pseudotuberculosis has a much lower number of insertion sequence (IS) copies than Y. pestis and so is genetically much more stable than the latter (30).…”
mentioning
confidence: 99%
“…In addition to LcrV and F1, six other Y. pestis antigens individually, namely, Psn [12], HmuR [12], PsaA (pH 6 antigen) [40], YadC [41], Pla, and YopE (unpublished data) have been vectored by Salmonella in our research studies. However, only immunization with RASVs delivering Psn [12] or YadC afforded partial protection against Y. pestis challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in our group showed that immunization with a mixture of the two RASVs, one delivering a carboxyl-terminal fragment of alpha toxin of Clostridium perfringens and the other a GST-NetB fusion protein induced protective immunity against C. perfringens in broiler chicks [42]. A similar approach could be applied for a mixture of two RASVs, one delivering LcrV, F1 and Psn antigens and the other another Y. pestis protective antigen, such as YopD [43], YscF [44], Ail [45] or YadC [41] to induce an optimal protective immune response.…”
Section: Discussionmentioning
confidence: 99%